Faktor Penyebab Menurunya Wisatawan Berkunjung Ke Objek Wisata Kadelang Fatang - Mani imelda blegur; Melki imamastri Puling Tang; Nehemia Fanpada; Jeni Soekarni Haan; padamani, mathias; Markus Guntur Ridho Famai; Julminggu Selly (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to examine the factors causing the decline in the number of touristsvisiting the Object KADELANG FATANG Beach District of Teluk Mutiara This study aims to examine the factors causing the decline in the number of touristsvisiting the Object Tourism Tirtayasa Beach District of Teluk Betung .Data collection with observation, interview and document ationt echniques. The results showed:The decrease of tourists visiting the beach Tirtayasa caused by the attractiveness ofthe beach kadelang Fatang is less attractive because of the beauty of the environment is lessbeautiful, cleanliness of the dirty environment and diversity of water games are notinteresting. Infrastructure is less good because it is difficult to get clean water and garbagedis system isnot good. The facilities are poorly maintained and incomplete. Unsafe security situation and lack of promotion and information. This research uses a descriptive method. Data collection with observation, interview anddocument ationt echni ques. Data analysis using scoring with Strutuges model. The results showed:The decrease of tourists visiting the beach kadelang Fatang caused by the attractiveness ofthe beach kadelang Fatang is less attractive because of the beauty of the environment is lessbeautiful, cleanliness of the dirty environment and diversity of water games are notinteresting. Infrastructure is less good because it is difficult to get clean water and garbagedi sposal system is not good. The facilities are poorly maintain edandin complete. Unsafe security situation and lack of promotion and information.